Nonlinear partial differential equations for scientists and engineers - Debnath Lokenath (Boston Birkhauser, 2005)
Contains updated modern examples and applications from areas of fluid dynamics, gas dynamics, plasma physics, nonlinear dynamics, quantum mechanics, nonlinear optics, acoustics, and wave propagation.
Keywords: Nonlinear differential equations; Partial differential equations